Microplastic Identification and Density In Coastal Sediments of Manado Bay - Angelyca P. Novadah Novadah; , Natalie D.C. Rumampuk; Nickson J. Kawung; Royke M. Rampengan; James J. H. Paulus; Darus S. J. Paransa (JURNAL PESISIR DAN LAUT TROPIS, 2025)
Most plastics originating from anthropogenic activities generate plastic waste in aquatic environments, which is difficult to degrade even when floating on the surface, suspended in the water column, or deposited in sediment. The increasing volume of plastic waste in marine waters requires global attention to develop rapid and effective solutions for managing plastic pollution. Microplastics are small plastic particles measuring less than 5 mm, and due to their small size, they are difficult to detect. Microplastics are categorized into two types: secondary microplastics and primary microplastics. This study aims to identify the types and quantify the density of microplastics based on their types and colors. Sediment samples were collected at two stations: station 1, located at the Tondano River estuary, and station 2, located on the coast of Mandolang Beach. The characteristics and density of microplastics were determined through sampling using a 50 meter transect line. The identification of shapes and colors and the counting of microplastics were conducted using a microscope. The results of this study show that Manado Bay is accumulated with microplastics characterized by three types fragments, fibers, and films and exhibiting colors such as black, blue, red, green, and white. The average microplastic density at station 1 was 73.33 particles/kg, and at station 2 was 44.67 particles/kg, indicating the average number of microplastics found in each kilogram of sediment sample from both stations. This finding indicates that the coastal area of Manado Bay has a considerable accumulation of microplastics. Keywords: microplastic, sediment, density, coast of Manado Bay, types of microplastic   Abstrak Sebagian besar plastik dari aktivitas antropogenik menghasilkan sampah plastik di lingkungan perairan, yang sulit terurai meskipun berada di permukaan, tersuspensi di kolom air, maupun mengendap di sedimen. Bertambahnya volume sampah plastik di perairan laut memerlukan perhatian global untuk mendapatkan solusi cepat dan efektif untuk penanganan pencemaran sampah plastik. Mikroplastik merupakan partikel plastik kecil yang berukuran <5 mm, dengan ukuran yang kecil mikroplastik sulit dideteksi. Mikroplastik terbagi menjadi dua yaitu mikroplastik sekunder dan mikroplastik primer. Penelitian ini bertujuan untuk mengidentifikasi jenis dan menghitung kepadatan mikroplastik, dengan mengidentifikasi berdasarkan jenis dan warna. Sampel sedimen diambil di 2 stasiun, stasiun 1 terletak di muara Sungai Tondano, stasiun 2 terletak di pesisir Pantai Mandolang. Karakteristik dan kepadatan mikroplastik ditentukan melalui pengambilan sampel yang dilakukan dengan metode garis transek sepanjang 50 meter. Identifikasi bentuk dan warna serta perhitungan jumlah mikroplastik dilakukan menggunakan mikroskop. Berdasarkan hasil dari penelitian ini diketahui Teluk Manado terakumulasi mikroplastik dengan karakteristik berdasarkan jenis berupa fragmen, fiber, dan film serta mikroplastik yang ditemukan memiliki warna hitam, biru, merah, hijau, dan putih. Kepadatan mikroplastik rata-rata pada Stasiun 1 sebesar 73,33 partikel/kg dan pada Stasiun 2 sebesar 44,67 partikel/kg, yang menunjukkan jumlah rata-rata mikroplastik dalam setiap 1 kilogram sampel sedimen di masing-masing stasiun. Temuan ini menunjukkan bahwa kawasan pesisir Teluk Manado terdapat akumulasi mikroplastik yang cukup signifikan. Kata kunci: mikroplastik, sedimen, kepadatan, pesisir Teluk Manado, jenis mikroplastik